2007
DOI: 10.1177/175899830701200203
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Review of Cold Intolerance Following Corrective Surgery for Dupuytren's Disease

Abstract: Cold intolerance is a cause of signifi cant morbidity following trauma to the upper limb and hand, yet very little research has been undertaken to investigate the phenomenon following elective hand surgery. This retrospective study, incorporating a postal questionnaire and case note review, investigates incidence and risk factors of cold intolerance in a series of patients who underwent corrective surgery for Dupuytren's disease. The incidence of cold intolerance following surgery for Dupuytren's disease was 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…However, the replantation group was significantly more cold-sensitive compared to the revascularisation group also when the patients without nerve/bone injury were excluded from the analysis. Cold hypersensitivity may occur after injury of any tissue and is recognised after Dupuytren’s surgery (McKirdy et al, 2007) and tendon injuries (Riaz et al, 1999). Ruijs et al (2007) found higher prevalence of cold hypersensitivity in patients with combined median and ulnar nerve injuries than those with injury to only one of these nerves.…”
Section: Discussionmentioning
confidence: 99%
“…However, the replantation group was significantly more cold-sensitive compared to the revascularisation group also when the patients without nerve/bone injury were excluded from the analysis. Cold hypersensitivity may occur after injury of any tissue and is recognised after Dupuytren’s surgery (McKirdy et al, 2007) and tendon injuries (Riaz et al, 1999). Ruijs et al (2007) found higher prevalence of cold hypersensitivity in patients with combined median and ulnar nerve injuries than those with injury to only one of these nerves.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanisms are not fully elucidated, but seem to involve a multifactorial etiology, including neural (Irwin et al 1997 ), vascular (Hope et al 2014 ), as well as humoral (Koman et al 1998 ) aspects. Cold sensitivity has previously been studied as a sequela to upper extremity injuries, such as digital and hand amputation (Lithell et al 1997 ; Tark et al 1989 ), hand fracture (Nijhuis et al 2010 ), peripheral nerve and brachial plexus injury (Novak et al 2012 ; Ruijs et al 2007 ), upper extremity arterial injury (Klocker et al 2012 ), flexor tendon repair (Riaz et al 1999 ), corrective surgery for Dupuytren’s disease (McKirdy 2007 ), carpal tunnel syndrome (Thomsen et al 2009 ), freezing cold injury (Carlsson et al 2014 ), and hand–arm vibration (HAV) syndrome (Carlsson et al 2010c ; Necking et al 2002 ). Injuries aside, cold sensitivity has also been described in relation to diabetes mellitus (Thomsen et al 2009 ), and rheumatic diseases (Merkel et al 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cold sensitivity can occur in connection with a variety of injuries and conditions. It is frequently reported after traumatic hand injuries [ 7 - 12 ], after surgically treated Dupuytren's contracture [ 13 ] and in patients with hand-arm vibration syndrome (HAVS) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%